Testing Antarctic resilience: the effects of elevated seawater temperature and decreased pH on two gastropod species. (17th December 2015) - Schram, Julie B.; Schoenrock, Kathryn M.; McClintock, James B.; Amsler, Charles D.; Angus, Robert A.
Abstract: Ocean acidification has been hypothesized to increase stress and decrease shell calcification in gastropods, particularly in cold water habitats like the western Antarctic Peninsula (WAP). There is limited information on how calcified marine benthic invertebrates in this region will respond to these rapidly changing conditions. The present study investigated the effects of elevated seawater temperature and decreased pH on growth (wet mass and shell morphometrics), net calcification, and proximate body composition (protein and lipid) of body tissues in two common benthic gastropods. Individuals of the limpet Nacella concinna and the snail Margarella antarctica collected from the WAP were exposed to seawater in one of four treatment combinations: current ambient conditions (1.5°C, pH 8.0), near-future decreased pH (1.5°C, pH 7.8), near-future elevated temperature (3.5°C, pH 8.0), or combination of decreased pH and elevated temperature (3.5°C, pH 7.8). Following a 6-week exposure, limpets showed no temperature or pH effects on whole body mass or net calcification. Despite no significant differences in whole body mass, the shell length and width of limpets at elevated temperature tended to grow less than those at ambient temperature. There was a significant interaction between the sex of limpets and pH. There were no significant temperature or pH effects on growth, net calcification, shell morphologies, or proximate body composition of snails. Our findings suggest that both gastropod species demonstrate resilience to initial exposure to temperature and pH changes predicted to occur over the next several hundred years globally and perhaps sooner along the WAP. Despite few significant impacts of elevated temperature or decreased pH, any response to either abiotic variable in species with relatively slow growth and long lifespan is of note. In particular, we detected modest impacts of reduced pH on lipid allocation in the reproductive organs of the limpet N. concinna that warrants further study.